2020
DOI: 10.9734/cjast/2020/v39i2530896
|View full text |Cite
|
Sign up to set email alerts
|

Brassinosteroids: A Multifunctional Phytohormone of Plant Development and Stress Responses

Abstract: Brassinosteroids (BRs) act as immune-modulators for generating plant growth and development. It regulated either activation or suppression of various key enzymatic reactions, activation of synthesis of protein, and generation of various defense modulating compounds for the plant kingdom. BRs play a vital role in regulating cellular differentiation, pollen development, fruit ripening, and quality seed formation.   BRs regulates the various physiological process including root growth during nutrient deficiency s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 158 publications
0
6
0
Order By: Relevance
“…BRI1 activates BZR1 and BES1 downstream TFs for inducing stress tolerance [19,47,133]. Upon BR perception, BR signals are relayed to BES1 and BZR1 via a signaling cascade, which eventually controls the transcription of genes regulated by the BRs [7,9,134,135]. BAK1, another LRR receptor kinase, interacts with BRI1 and acts as a co-receptor.…”
Section: Brs Signaling In Plantsmentioning
confidence: 99%
“…BRI1 activates BZR1 and BES1 downstream TFs for inducing stress tolerance [19,47,133]. Upon BR perception, BR signals are relayed to BES1 and BZR1 via a signaling cascade, which eventually controls the transcription of genes regulated by the BRs [7,9,134,135]. BAK1, another LRR receptor kinase, interacts with BRI1 and acts as a co-receptor.…”
Section: Brs Signaling In Plantsmentioning
confidence: 99%
“…Drought tolerance is a complex trait that encompasses growth stabilisation, water relations and several stress-sensing/response mechanisms 29 . In a physiological approach, drought sensing and response comprise, among others, reactive oxygen species (ROS) generation, detection and control via enzymatic and non-enzymatic paths 29 that BRs can regulate to prevent ROS-induced injuries 30 . When analysing the DI-31 effects on Munasqa antioxidant response, our findings confirmed that the analogue, independently of the water availability, favoured the enzymatic scavenging of superoxide radicals (O 2 − ) and hydrogen peroxide (H 2 O 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al (2013) also observed that the use of CK favored the nutritional status of nitrogen during heat stress in creeping bentgrass. Praveena et al (2020) report that the use of brassinosteroids favors nutrient content in plants under multiple abiotic stresses. This result may be due to the fact that these compounds increase the contents of osmolytes within the roots, favor mass flow, prevent the degradation of proteins responsible for nitrogen uptake, and promote the expression of transport channels (Liu et al 2020;Praveena et al, 2020;Kothari and Lachowiec, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…(2013) also observed that the use of CK favored the nutritional status of nitrogen during heat stress in creeping bentgrass. Praveena et al. (2020) report that the use of brassinosteroids favors nutrient content in plants under multiple abiotic stresses.…”
Section: Discussionmentioning
confidence: 99%